Geothermal heat flux of Ridge B region in Antarctica inferred from basal dry–wet distribution - Shinan Lang; Mingzhu Yang; Xiangbin Cui; Lin Li; Xiaofeng Wang; Jingxue Guo; Jamin S. Greenbaum; Bo Sun; Martin J. Siegert (Journal of Glaciology)
Ridge B is one of the least studied areas in Antarctica but has been considered to be a potential location for the oldest ice on Earth. Among important parameters for calculating where very old ice may exist, geothermal heat flux (GHF) is critical but poorly understood. Here, GHF is determined by quantifying the transitions between dry and wet basal conditions using a radioglaciological method applied to airborne radio-echo sounding data. GHF is then constrained by a thermodynamic model matched to the transitions. The results show that GHF in Ridge B varies locally and ranges from 48.5 to 65.1 mW m−2, with an average value of 58.0 mW m−2, which is consistent with the current known GHF constrained by subglacial lakes and derived from Vostok ice core temperature measurements. Our work highlights the value of considering local GHF when locating the oldest ice in this potential region or other regions.